Hambatan yang Dialami Keluarga dalam Menjalankan Program Pelayananan Paliatif Pasien Kanker Stadium Lanjut - Dasat, Mariam; Khasanah, Uswatul; Mulyono, Sigit; Anggraini, Dian (Journal of Telenursing (JOTING), 2023)
This study aims to explore the obstacles experienced by families in providing palliative services to advanced cancer patients. The method used is a qualitative research design with a phenomenological approach. The research results showed that there were three themes found in the family's perception of undergoing a palliative care program for advanced cancer patients, namely that the patient should not be accompanied during examinations, the patient's companion cared for him while working, and was financially burdened. In conclusion, the obstacles experienced by families in undergoing palliative care for advanced cancer patients are caused by the family's low socioeconomic status, so even though the government provides free treatment and care, transportation to home is your responsibility. Apart from that, when the patient was undergoing treatment at the hospital, he was in COVID-19. Keywords: Family Barriers, Palliative Services, Cancer.